2016
DOI: 10.1002/pd.4799
|View full text |Cite
|
Sign up to set email alerts
|

First trimester cystic hygroma: does early detection matter?

Abstract: Cystic hygroma detected when crown-rump length measures below 45 mm have lower rates of chromosomal abnormalities and a higher proportion of normal birth outcomes when compared to those detected later in the first trimester. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
0
18
2
Order By: Relevance
“…At least half of the septated cystic hygroma cases were reported to be coexisting with chromosomal abnormalities. Recently, Scholl et al reported that abnormal karyotype rates were 43.4% in fetuses with cystic hygroma detected when CRL measured below 45 mm and 73% fetuses with CRL was 45-84 mm (7). If nuchal translucency measurement was above 2 mm, 60% were related with abnormal karyotype and one fourth of these cases were detected to have trisomy 21.…”
Section: Discussionmentioning
confidence: 99%
“…At least half of the septated cystic hygroma cases were reported to be coexisting with chromosomal abnormalities. Recently, Scholl et al reported that abnormal karyotype rates were 43.4% in fetuses with cystic hygroma detected when CRL measured below 45 mm and 73% fetuses with CRL was 45-84 mm (7). If nuchal translucency measurement was above 2 mm, 60% were related with abnormal karyotype and one fourth of these cases were detected to have trisomy 21.…”
Section: Discussionmentioning
confidence: 99%
“…found that fetuses with a cystic hygroma detected at an early gestation (when the CRL was 45 mm and below) often had a normal karyotype (26 fetuses out of 28 with a cystic hygroma at CRL 45 mm or below). 17 The rate of IVF conceptions was considerably higher in our cohort than in the general obstetric population, since 14.1% of pregnancies were conceived via IVF, compared with 4.7% of births in Australia that were conceived using some type of assisted reproductive technology. 18 This is likely due to the practice's affiliation with an IVF provider, who refer a significant number of their patients to this clinic.…”
Section: Main Findings and Clinical Implicationsmentioning
confidence: 66%
“…In cases where a foetus is referred with a prenatal diagnosis of cystic hygroma (usually in the setting of foetal hydrops), we have also found that these cystic masses can ‘resolve’ [55], much like the appearances of ventriculomegaly, thus the role of PMUS is to review associated structural anomalies rather than identify the cystic hygroma itself. Associated anomalies (commonly intracranial in origin) are estimated to occur in 36–55.6% of cases, and usually related to an abnormal genetic karyotype [56, 57] which will have implications for prenatal counselling in future pregnancies [58].
Fig.
…”
Section: Systems Reviewmentioning
confidence: 99%